Lesotho Poverty Assessment : Progress and Challenges in Reducing Poverty - World Bank (World Bank, Washington, DC, 2019)
This report examines progress and challenges in reducing poverty in Lesotho. Lesotho's poverty rate is lower today than it was 15 years ago. However, with a poverty rate of 49.7 percent in 2017, poverty remains widespread. Economic vulnerability is high, with more than 75 percent of the population either poor or vulnerable to poverty. This suggests that most of the population lack economic opportunities and are deprived on multiple fronts. Urban areas experienced greater poverty reduction due to improvements in education and increases in incomes from well-paying jobs, largely in the services sector. In rural areas, poverty stagnated due to slow growth in agricultural incomes, a fall in remittances and vulnerability of the rural population to weather shocks. Despite the growing urban-rural poverty divide, inequality fell as a result of expansion of social protection and an increase in wage incomes among the poor. In spite of this, Lesotho remains one of the 20 percent most unequal countries in the world. A combination of policies that improve human capital, promote job creation and address high unemployment, increase agricultural productivity, together with those that build resilience against economic and environmental shocks, would boost shared prosperity and accelerate poverty reduction in Lesotho.